Additive stabilization of SEI on graphite observed using cryo-electron microscopy. Issue 9 (29th July 2021) - Han, Bing; Zou, Yucheng; Xu, Guiyin; Hu, Shiguang; Kang, Yuanyuan; Qian, Yunxian; Wu, Jing; Ma, Xiaomin; Yao, Jianquan; Li, Tengteng; Zhang, Zhen; Meng, Hong; et al.
Abstract : Cryo-electron microscopy study finds that EC-based electrolyte can exfoliate the graphite surface and destabilize the SEI. Useful additives including FEC, DTD, TPP, and VC can form a stable SEI to protect the graphite anode. Abstract : Revealing the atomic structures of the solid electrolyte interphase (SEI) is challenging due to its sensitivity to electron beam and environmental factors such as moisture and oxygen. Here, we unveiled the atomic structures and phase distribution of the fragile solid electrolyte interphase (SEI) on graphite using ultra-low-dosage and aberration-corrected cryo-transmission electron microscopy (cryo-TEM). It is known that propylene carbonate electrolyte can exfoliate a graphite anode and damage its structural integrity. Surprisingly, ethylene carbonate–diethyl carbonate can also damage the surface of the graphite anode by exfoliation even with an initial formation protocol of constant-current charging (0.05C) for three hours and then 0.1C for another 3 hours at 45 °C: we hypothesize that the exfoliated graphene layers embedded in the SEI enhance local electron channeling, which induces an ever-growing, thick SEI layer with randomly distributed graphene, Li2 O, and Li2 CO3 nano-crystals. Using the same formation protocol but with 1 wt% vinylene carbonate (VC), triphenyl phosphate (TPP), or ethylene sulfate (DTD) or 10 wt% monofluoroethylene carbonate (FEC) as the additive is found to cause solid deposition prior to the graphite exfoliation instability, which generates a stable and thin SEI (<90 nm) on the graphite surface which prevents further exfoliation of graphite and rapidly suppresses the decomposition of electrolyte in the later cycles. When using a slower formation protocol including 2 cycles between 3.0 and 4.2 V at a rate of 0.01C at room temperature, graphite exfoliation is dramatically reduced, but is still observable initially.